Order hardening of platinum alloys - Towle, Nicholas Richard (Centre for Materials Engineering, 2016)
The hardening behaviour of three cold-worked platinum alloys, Pt 5 at% Mo, Pt 5 wt% Ru and Pt 5 wt% Cu, has been investigated through a systematic series of heat treatments. All three of the experimental alloys showed a hardness increase during annealing within a specific temperature range. The hardness of the Pt-Mo and Pt-Ru alloys was found to increase rapidly at annealing temperatures above the recrystallisation temperature, with the final hardness similar to the original coldworked hardness. The hardness of Pt-Cu showed an increase of up to 30% at low annealing temperatures of between 200°C and 500°C. In addition, the Pt-Cu alloy also showed the increased hardness found in Pt-Mo and Pt-Ru at high annealing temperatures, but the hardness increase was not to the same extent. Specimens subjected to the annealing treatments were studied by means of optical, scanning electron and transmission electron microscopy, in order to determine the effect of annealing on microstructure and structural order. Resistivity, XRD and OTA techniques were employed in order to study the mechanisms of ordering with temperature, but these techniques did not produce any significant results. It was concluded that the most likely cause for the hardness increase observed in all three experimental alloys was due to a change in structural order upon annealing. The Pt-Mo and Pt-Ru alloys hardened through an increase in short-range order at annealing temperatures above the recrystallisation temperature. The Pt-Cu alloy hardened through the development of long-range order on annealing between 200°C and 500°C. This increase in hardness was in· addition to the high dislocation density in the alloy specimen due to prior cold-work.